2008
DOI: 10.1118/1.2968337
|View full text |Cite
|
Sign up to set email alerts
|

Closed bore XMR (CBXMR) systems for aortic valve replacement: Investigation of rotating‐anode x‐ray tube heat loadability

Abstract: In order to improve the safety and efficacy of percutaneous aortic valve replacement procedures, a closed bore hybrid x-ray/MRI ͑CBXMR͒ system is proposed in which an x-ray C-arm will be positioned with its isocenter Ϸ1 m from the entrance of a clinical MRI scanner. This system will harness the complementary strengths of both modalities to improve clinical outcome. A key component of the CBXMR system will be a rotating anode x-ray tube to produce high-quality x-ray images. There are challenges in positioning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…An air-cored electromagnet ͑Stangenes Industries, Palo Alto, CA͒ was used to produce B and is described in detail elsewhere. 12 The electromagnet was able to produce a maximum B of 23 mT at its center along its central axis and field uniformity was within Ϯ5% over a cubic region with 12 cm sides around its center. This magnet was able to provide a magnetic field component perpendicular to the electron beam of comparable strength to the fringe field components B r and B z of the MRI scanner, both of which can cause electron beam deflection depending on x-ray tube orientation.…”
Section: Iiib Focal Spot Deflectionmentioning
confidence: 94%
See 3 more Smart Citations
“…An air-cored electromagnet ͑Stangenes Industries, Palo Alto, CA͒ was used to produce B and is described in detail elsewhere. 12 The electromagnet was able to produce a maximum B of 23 mT at its center along its central axis and field uniformity was within Ϯ5% over a cubic region with 12 cm sides around its center. This magnet was able to provide a magnetic field component perpendicular to the electron beam of comparable strength to the fringe field components B r and B z of the MRI scanner, both of which can cause electron beam deflection depending on x-ray tube orientation.…”
Section: Iiib Focal Spot Deflectionmentioning
confidence: 94%
“…11͒ in which a C-arm x-ray system is placed close to ͑Ϸ1 m͒ the entrance of a 1.5 T MRI scanner. 12 This system will harness the complementary strengths of both modalities by providing high quality fluoroscopy and angiography using x-ray imaging and cardiac anatomical imaging using MRI without the risks associated with patient transfers over long distances ͑several meters͒. 12 The challenges in the construction of this system have been outlined in previous publica-tions, most of which have been overcome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A flat-panel detector and a rotating-anode x-ray tube are mounted on the C-arm. 11 Previous work showed that the electron beam in the x-ray tube used to produce x rays 12 at the focal spot on the anode can be deflected 13,14 by the magnetic fringe field of the MRI scanner. 15 The electron beam deflection causes a shift in the irradiated field of view.…”
Section: Introductionmentioning
confidence: 99%